The independence of justice as proxy for the rule of law in the EU Case study – Romania (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2021)
The concept of rule of law has been addressed as a formal or as a substantive notion. Although it does not enjoy a generally accepted academic definition and its practical transposition varies according to the implementing State, it is a founding value and a functional necessity for the European Union. However, the recent case law of the ECJ on this matter seems to narrow down the concept of rule of law to one of its elements, namely the independence of justice. This is due to the specific context in which the ECJ had to develop the standard, and which is linked to the rule of law backsliding noticed over the past few years in Hungary and Poland and, to some extent, in Romania. In the specific case of Romania, the ECJ displayed a moderate stance, possibly due to the fact that an institutionalised monitoring of the rule of law has been in place since 2007.
Keywords: Rule of law; independence of justice; Romania